PENGARUH PENAMBAHAN MULTI NUTRIENT SAUCE DALAM RANSUM TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK PADA DOMBA - Yogi Ramdani, Erwanto, Farida Fathul, dan Liman (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to investigate the effect of adding multi nutrient sauce to rations on the digestibility of dry matter and organic matter in sheep. This research was conducted in May--July 2019 in Kebagusan Village, Gedong Tataan District, Pesawaran Regency. Analysis of feed ingredients and feces was carried out at the Animal Nutrition and Feed Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This research was conducted experimentally using the Randomized Block Design (RBD) method. Sheep were divided into six groups based on body weight, namely group 1 (11,18--13,18 kg), group 2 (13,97--14,13 kg), group 3 (14,31--14,51 kg), group 4 (14,89--15,91 kg), group 5 (16,35--16,66 kg), and group 6 (17,15--17,77 kg). Each group consisted of 3 sheep. Treatment given were R0: basal ration formulated by farmer (forage silage + cassava byproduct), R1: R0 + 5% multi nutrient sauce, R2: R0 + 10% multi nutrient sauce. The results showed that the addition of 10% multi nutrient sauce was the best treatment that could improve the digestibility of dry matter and organic matter in sheep. Key word : Multi nutrient sauce, Dry matter digestibility, Digestibility of organic matter, Sheep.